Rheostatic Functions of Mast Cells in the Control of Innate and Adaptive Immune Responses. Issue 9 (September 2017) - Frossi, Barbara; Mion, Francesca; Tripodo, Claudio; Colombo, Mario P.; Pucillo, Carlo E.
Abstract : Mast cells are evolutionarily ancient cells, endowed with a unique developmental, phenotypic, and functional plasticity. They are resident cells that participate in tissue homeostasis by constantly sampling the microenvironment. As a result of their large repertoire of receptors, they can respond to multiple stimuli and selectively release different types and amounts of mediator. Here, we present and discuss the recent mast cell literature, focusing on studies that demonstrate that mast cells are more than a switch that is turned 'off' when in the resting state and 'on' when in the degranulating state. We propose a new vision of mast cells in which, by operating in a 'rheostatic' manner, these cells finely modulate not only immune responses, but also the pathogenesis of several inflammatory disorders, including infection, autoimmunity, and cancer. Trends: New findings suggest that it is shortsighted to limit the classification of mast cells to two subtypes; indeed, each specific tissue has a unique mast cell type that differs significantly from those of other tissues. Mast cells continuously sample the microenvironment, working to maintain tissue homeostasis and contribute immediately to the immune response to non-self-antigens. A network of activating and inhibitory stimuli can modulate mast cell activity. A mast cell is more than a switch that is turned 'off' when in the resting state and 'on' when needed; instead, mast cells show a range of modulated responses that contribute to the fine-tuning of the immune response.